Déficit hídrico e sua atenuação em plantas de fisális (Physalis angulata L.) - Leite, Romeu da Silva (2019)
Physalis production is little studied in Brazil, especially in the semiarid region, where water deficit is a major constraint for agricultural production, promoting the reduction of yield and plant growth. It's known that exogenous application of nitric oxide (NO) may play an important role in drought-tolerant plants in large crops or underexploited species, such as Physalis angulata. This study aimed at assessing the physiological responses and growth characteristics of P. angulata plants under water deficit, as well as mitigation potential of NO. Water deficit conditions were simulated in two experiments in greenhouse, applying different water availability (100%, 80%, 60%, 40% and 20% of the maximum retention capacity) in the experiment Iand sodium nitroprusside (SNP) concentrations (0, 25, 50, 75 and 100 μM), an exogenous NO donor in the experiment II. For this, water relations, gaseous exchanges, sugar accumulation, foliar activity of nitrate reductase and growth parameters were evaluated. Water relations (water potential and relative water content) were affected mainly in plants under severe water deficit (20%), as well as gas exchanges, with reduction in carbon assimilation, internal carbon, stomatal conductance and transpiration. However, for these plants were observed increases in leaf temperature and water use efficiency. Plants accumulated sugars as a mechanism of acclimatization to severe water deficit, while nitrate reductase activity was reduced. There was maintenance of total dry matter mass accumulation and leaf area under moderate and severe levels of water deficit. Exogenous application of nitric oxide promoted symptoms attenuationon photosynthetic performance, notably carbon assimilation, water use efficiency and chlorophyll content. The NO application promoted a direct relationship between sugar accumulation and leaf water potential. Similarly, NO attenuated symptoms of water scarcity on plant growth, especially plant height, dry matter accumulation and leaf area. P. angulata plants develop important strategies to tolerate water deficit, which may contribute to the establishment of crops under low water availability. Low concentrations of SNP are indicated to mitigate negative effects of water deficit, improving photosynthetic rates, maintenance of leaf water potential and growth